La justicia de paz y acceso al registro de las escrituras imperfectas - Ortiz Pasco, Jorge (2019)
The author of this text makes a description of the functioning of an institutionthat is sometimes set aside of the legal literature: the Justice of the Peace. Justiceof the Peace is a judicial authority that has a great importance in Peru, given thenumber of people that are not able to come before regular courts, in order to solvetheir controversies. This text does not focus in the role of the Justice of the Peacein solving controversies, but in its role to act as a Notary Public. In that sense, incities or provinces where there is not a Notary Public, this role is fulfilled by theJustice of the Peace. Among the Notary tasks assumed by the Justice of the Peaceis to issue public deeds, which have basically the same quality as the ones that anyNotary Public would issue. These instruments, that are called “imperfect publicdeeds”, have been the matter of a series of binding precedents by the “TribunalRegistral”, the public entity in charge of reviewing –as a last stage of proceeding–the decisions of the registrars relating to imperfect public deeds. The author refersto them in an effort to explain the context, the history and the importance of therole of the Justice of the Peace in Peru.